Factors Related to the Number of Antral Follicles on InVitro Fertilization (IVF) - Raharja, Fransiskus C; Suwiyoga, Ketut; Wardhiana, IPG (Indonesian Socety of Obstetrics and Gynecology, 2016)
Objective: To determine factors which are related to the number of antral follicles on infertile patients. Method: This cross sectional study was conducted in In-Vitro Fertilization (IVF) clinic of Graha Tunjung, Sanglah hospital, Bali. All fertile patients following the IVF program were calculated the number of antral follicles in both ovarian using transgene USG. This sample was recruited by random sampling from April 1st, 2001 to April 30th, 2011. We analyzed the data using Chi square test through SPSS for Windows 17.0 version. Result: Of 102 samples, the mean of patients’ age was 32.9% (SD 4.6) years old. From 72 patients (70.6%) experienced above 3 years of infertile period, the primary infertile was on 69 patients (67.7%). There was a relationship between patients’ age and the number of antral follicles significantly (prevalence ratio (PR) 1.41; 95% CI 1.11- 1.79). Meanwhile, the number of antral follicles and type of infertile (PR 1.02; 95% CI 0.76-1.37) also infertile period (PR 0.95; 95% CI 0.72-1.27) were not associated significantly. Conclusion: Patients’ age has an association with the number of antral follicles on IVF. [Indones J Obstet Gynecol 2016; 4-2: 75-77] Keywords: age, infertile, infertile period, number of antral follicles and type of infertile